2018
DOI: 10.1080/08990220.2018.1444599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinect-based virtual reality game training on upper extremity motor recovery in chronic stroke

Abstract: To conclude, our results suggest that the adjunct use of Kinect-based VR training may contribute to the improvement of UE motor function and AROM in chronic stroke patients. Further studies with a larger number of subjects with longer follow-up periods are needed to establish its effectiveness in neurorehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 29 publications
3
73
0
1
Order By: Relevance
“…In some studies, the score obtained or time taken, act as an index of performance and is related to motor skills. For example, in the serious game Good View Hunting [46] the participant is asked to remove the dirty regions of the screen or to clean a water stain, fog, children's drawings or car dust using the affected limb.…”
Section: Artificial Vision -Optical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, the score obtained or time taken, act as an index of performance and is related to motor skills. For example, in the serious game Good View Hunting [46] the participant is asked to remove the dirty regions of the screen or to clean a water stain, fog, children's drawings or car dust using the affected limb.…”
Section: Artificial Vision -Optical Systemsmentioning
confidence: 99%
“…The score is measured through the speed of execution. In Hong Kong Chef [46], that consists of two sections, whose common objective is to prepare food (take and leave ingredients, mix them, cut them and cook them). Again, the score is measured through [53].…”
Section: Artificial Vision -Optical Systemsmentioning
confidence: 99%
“…1) NIHSS: aims to quantify neurological deficits through items that address the level of consciousness, speech, language, visual field, somatognosia, eye movement, strength, coordination, and sensitivity. The maximum score is 42, indicating a high neurological score 15 ;…”
Section: Neurological Characteristicsmentioning
confidence: 99%
“…Therefore, virtual reality is still a promising tool. Some authors have reported that VRT can be combined with conventional rehabilitation to improve upper limb function after stroke 15,16 . The clinical situations wherein VRT may best be used have not yet been established in the literature.…”
mentioning
confidence: 99%
“…However, the approach remains mostly reserved to specialized facilities, and consequently is available for limited amounts of time for a limited number of patients. In an attempt to cover the needs for affordable home rehabilitation, gaming class motion sensors and systems have been adapted to "serious games" -e.g., Nintendo Wii ® (Nintendo) [10], Playstation EyeToy ® (Sony) [11,12], Xbox 360/XboxOne ® (Microsoft) [13]. Although the sensation they provide is less realistic (as the avatar of the user is usually placed inside the virtual environment -system put the user inside the computer instead of projecting the generated environment around him), these systems do provide some of the features that constitute the theoretical basis of the approach [14].…”
Section: Introductionmentioning
confidence: 99%